The Effect of Decalcified Root Surfaces on Dentinal Bond Strength. Issue 6 (2nd June 2016) - Ozer, Fusun; Sher, Michael; Daneshmehr, Leila; Karabekiroglu, Said; Sinmazisik, Gulden; Unlu, Nimet; Blatz, Markus B.
Abstract : Microtensile bond strengths of current dentin adhesives to intact and decalcified root surfaces were evaluated. Two hundred and twenty-four extracted human incisors were divided into two groups as intact (IRD) and decalcified (DRD). The roots of DRD teeth were placed in a demineralization solution to produce artificial carious-like lesions. Root surfaces were slightly ground and treated with either Scotchbond Multi-Purpose (SMP), Adper Single Bond Plus (SBP), Adper Easy Bond (AEB), Scotchbond SE (SSE), Clearfil SE Bond (CSE), Clearfil Protect Bond (CPB), Clearfil Tri-S Bond (CTS), FL-Bond II (FLB), XP Bond (XPB), iBond (IB), AdheSE Bond (ASE), Optibond Solo Plus (OSP), Prelude Dental Adhesive (PDA), and G-Bond (GB). Composite build-ups were formed on the bonded surfaces. After thermocycling, hour-glass shaped specimens with an area of 1 mm 2 at the bonded interface were subjected to microtensile testing. Resin–dentin interfaces were observed with SEM. Kruskal Wallis and Mann Whitney-U tests were used for statistical analysis. There was not significant difference between bond strengths to intact and decalcified dentin, with the exception of ASE and CSE, which had higher values to IRD (p < 0.05). SSE and CTS were the adhesives that showed higher bond strengths to DRD than to IRD, however the difference was not significant (p > 0.05). The self-etch adhesives performed better on both IRD and DRD surfaces than etch-and-rinse systems.